A method to measure the damping introduced by linear guides in large milling machines. (15th May 2022) - Oleaga, I.; Zulaika, J.J.; Campa, F.J.; Hernando, J.
Highlights: Theoretical-experimental method to calculate the damping of linear guides. Calculating real damping contribution of each linear guide assembled in a machine. Identifying linear guides that provide less damping than their capacities. Identifying linear guides that can add more damping if they are replaced. Abstract: Simulation of the dynamic behavior of a milling machine requires accurate stiffness, inertia, and damping values. Unlike the properties of stiffness and inertia, damping values are not generally available in the bibliography, which only contains reference values. In the present work, a method is proposed to measure the damping introduced by one linear guide when assembled in large-scale milling machines, unlike current available methods which measure the damping capacities of such guides. Linear guides of same size and type can introduce different damping values at different joints even in the same machine, so that these damping values depend both on the damping capacities of the guide and on the dynamic properties of the joint. This method will allow identifying linear guides that can introduce highest damping values. This identification has been done first by measuring frequency responses at the linear guides of the machine and calculating the modal vectors of that linear guides with finite element models. Secondly, energy dissipation that takes place in these guides has been represented by associating the damping of each linear guide in a discrete way. Next, the method has been validated on a real large machine by comparing estimated and measured frequency responses at tool center point. One immediate advantage of this method will be to improve the dynamic frequency responses of milling machines, and therefore, their productivity for the manufacturing processes in which chatter phenomena arise.